The association between empathy ability and attitudes toward children with disabilities in inclusive physical education classes among primary students: the mediating role of friendship quality - Ling, Wenwei; Wang, Dandan; Xu, Xin; Zhu, Dong; Wu, Xueping; Zhang, Lei (Frontiers in Psychology, 2025)
BackgroundThe acceptance and inclusion of children with disabilities, especially in inclusive physical education classes, is crucial for their social integration and psychological well-being. To examine the relationship between friendship quality, empathy and attitudes of children without disabilities toward their peers with disabilities in inclusive physical education classes.MethodsThe Children’s Attitudes Toward Integrated Physical Education–Revised, Friendship Quality Questionnaire, and The Chinese version of the Interpersonal Reactivity Index instruments were used to investigate the attitudes of children without disabilities toward the participation in physical education classes of their peers with disabilities, the quality of their friendships, and their ability to empathize, respectively. Descriptive statistics, Pearson’s correlation analysis, linear regression, and mediation effects were used for data analysis.ResultsGirls without disabilities showed more positive attitudes than boys without disabilities toward the inclusion in physical education classes of children with disabilities (total score t = −3.92, p < 0.001). Disability attitudes were significantly and positively correlated with friendship quality (r = 0.22, p < 0.001) and the ability to empathize (r = 0.16, p < 0.01). Empathy positively predicted disability attitudes (adjusted R2 = 0.055, F = 13.555, p < 0.001), and friendship quality mediated the relationship.ConclusionFriendship quality plays a key role in mediating the effect of empathy on attitudes of children without disabilities toward their peers with disabilities. Enhancing students’ empathy indirectly improves their attitudes toward disabilities by strengthening friendships.